The Effect of Transcranial Direct Current Stimulation Combined with Visual Cueing Training on Motor Function, Balance, and Gait Ability of Patients with Parkinson’s Disease - Lee, Si-a; Kim, Myoung-Kwon (Medicina (Kaunas, Lithuania), 2021)
Background and Objectives: The purpose of this study was to investigate the effects of transcranial direct current stimulation (tDCS) on motor function, balance and gait ability in patients with Parkinson’s disease (PD). Materials and Methods: For the experiment, 30 patients with PD were randomly assigned to the experimental group (n = 15) and the control group (n = 15). Visual cueing training was commonly applied to both groups, the experimental group applied tDCS simultaneously with visual training, and the control group applied sham tDCS simultaneously with visual training. All subjects were pre-tested before the first intervention, post-tested after completing all 4 weeks of intervention, and followed-up tested 2 weeks after the completing intervention. The tests used the Unified Parkinson’s Disease Rating Scale (UPDRS) for motor function assessment, Functional Gait Assessment (FGA) for balance assessment, Freezing of Gait Questionnaire (FOG-Q) and the GAITRite system for gait ability assessment. Among the data obtained through the GAITRite system, gait velocity, cadence, step time, double support time, and stride length were analyzed. Results: The experimental group showed a significant decrease in UPDRS and a significant increase in FGA and cadence after the intervention. In addition, UPDRS and cadence showed a significant difference in the follow-up test compared to the pre-intervention test. Conclusions: This study suggests that the application of tDCS to the supplementary motor area of PD patients is useful as an adjuvant therapy for rehabilitation training of PD patients.